Queen Charlotte [large type] - Quinn, Julia, 1970-; Rhimes, Shonda (Quinn, Julia, 1970- Bridgerton series., 2023)
In 1761, German Princess Charlotte of Mecklenburg-Strelitz marries King George III, and in her new role, she navigates the intricate politics of the court while guarding her heart as she fights for herself, her husband, and for all her new subjects who look to her for guidance and grace.